PENERAPAN LATIHAN SHADOW DALAM UPAYA MENINGKATKAN KELINCAHAN PADA MATERI PERMAINAN BULUTANGKIS - Sukesih Sukesih (Universitas Muhammadiyah Purwokerto, 2015)
The aim of this research was to get the information about an effort to improve the students agility through shadow training. The action hypothesis of this research was as follow: by using shadow training, the students’ learning achievement of the six graders of SD Negeri 2 Sokaraja in academic year 2012/2013 got improvement. The method and the design of this research was Classroom Action Research (CAR) held in 3 research cycles, each cycle had planning, acting, observing, and reflecting. The variable of this research was independent variable in this research was an effort to improve agility. The subjects of this research were the six garders of SD Negeri 2 Sokaraja in academic year 2012/2013, with 20 students (10 boys and 10 girls). The instrument of the research and the data used in this research was gained from the students’ performance of psychomotor, affective test and cognitive test as well as the activity of observation by two observers. Based on the result of the data analysis, it could be concluded that the implementation of shadow training could improve the students’ agility and learning achievement for the six graders of SD Negeri 2 Sokaraja in academic year 2012/2013